(untitled) (Mustansiria Dental Journal, 2018)
Background and objectives: The contemporary demand for esthetic less visible ceramic bracket is associated with the disadvantage of complicated and difficult debonding procedure at the end of the treatment. The aim of this study was to evaluate the water atomized laser system for debonding ceramic brackets. Method: Eighty maxillary premolars were divided into two main groups. In group-1, poly crystalline ceramic brackets (Reflections, Ortho technology, USA) were bonded to buccal enamel surface. In group-2, mono crystalline ceramic brackets (PURE, Ortho Technology USA). Were bonded to buccal enamel surface. For all teeth, the same bracket bonding system was used. Following debonding with both water atomized laser device and manual debonding instrument, teeth and brackets were examined under 10X magnification for assessment of bracket failure (fracture) and of residual adhesive on the enamel surface using a modified adhesive remnant index (ARI). Enamel surfaces were visualized with trans-illumination prior to bonding and after removal of the residual adhesive, so the effect of the debonding forces could be determined. The numbers of the fractured brackets were counted. Results: Statistical analysis showed a significant difference in the ARI between debonding with water atomized laser and utility-debonding pliers in such away more adhesive remnant was revealed on teeth with laser debonding. Also less enamel damage recorder with laser group debonding compared with conventional debonding procedure, which was statistically significant, additionally more bracket fractures encountered with conventional debonding than debonding with laser apparatus, which was highly significant statistically. Conclusions: Debonding of ceramic orthodontic brackets could be done with water atomized laser apparatus with minimal enamel surface cracks and lesser chance of bracket fractures.